Introductory Reflections on the Protection of the Environment in Regional Jurisprudences - Raisz, Anikó; Krajnyák, Enikő (Human Rights and Environmental Protection from a Central and Eastern European Perspective, 2026)
This piece offers an introductory overview of the environmental jurisprudence of regional adjudicatory bodies, as elaborated in the forthcoming chapters of the present book. It positions the growing body of case law from the European Court of Human Rights (ECtHR), the European Committee of Social Rights (ECSR), the Court of Justice of the European Union (CJEU), the Inter-American Court of Human Rights (IACtHR), the Inter-American Commission on Human Rights (IACHR), the African Court of Human and Peoples’ Rights (ACtHPR), and the African Commission on Human and Peoples’ Rights (ACHPR) within the broader development of the protection of the environment in international human rights law. The study further examines the recognition of the right to a healthy environment across the different regional systems, as one of the key points of normative divergences. Rather than offering an exhaustive analysis, these introductory reflections lay the conceptual framework and identify key issues that will be examined in greater depth in the subsequent chapters.